PENJADWALAN PEMBANGUNAN GEDUNG PARKIR RUMAH SAKIT TELOGOREJO, SEMARANG - , IRMALIA NURSITA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Hospital parking deck Telogorejo in Semarang built to fulfill vehicle parking capacity. Parking area today do not fulfill the needs that require extensive additional parking capacity in order to fulfill capacities parking lot. Before the construction carried out, the necessary time schedule of all the events leading to the activities to be carried out. Time schedule plans are used as a comparison with the beginning of the realization of the work that has been carried out in the field. Some problems may occur during the execution of the work and may cause delays. In Building Project Hospital Parking Telogorejo of the S-curve data can be seen that : at week 1 to week 14 Building Project Hospital Parking Telogorejo delayed. The delay occurred because of the weather (rain) and change of shop drawing. The maximum delay that occurred in Building Project Telogorejo Hospital Parking can reach 0,7%. Acceleration which began the week 17th Building Project Hospital Parking Telogorejo produce progress with 17,9% faster speed, even faster than the planning of 2,6% of the progress of the plan.